(3GPGYI GdTHGH h GdQjGVI hhGbY GdTHGH GdeUQj (B/s - (3SdjeGf QRb,SGMjI s ((3GdbGgQI (B:s (3ecJHI GdGfLdh GdeUQjI ,s, 1989)
(3hGbY GdTHGH GdeUQj h bVGjGg(B,(3GdGWGQ GdefgLj dOQGSI(B,(3fJGFL GdOQGSI GdJMdjdjI deVehf HQGeL GdGPGYIs
Keywords: (3GdTHGHs; (3GPGYIs; (3GdQjGVIs